Physical and Physiological Demands of Official Beach Soccer Match-Play in Relation to Environmental Temperature - Thiago Carvalho; Vincenzo Rago; João Brito; Priscyla Praxedes; Marco Abreu; Davi Silva; Sara Pereira; Magni Mohr; Ivan Baptista; José Afonso (Sports)
Environmental temperature (Te) is a main atmospheric parameter that may affect the physical and physiological demands of outdoor sports. Thus, this study aimed to examine the relationship of Te with the physical and physiological demands of beach soccer match-play. Physical and physiological demands were collected from 60 male players during Portuguese elite beach soccer championship matches using a 10 Hz wearable global positioning system, heart rate, and the rate of perceived exertion (RPE). A bilateral counter-movement jump (CMJ) test assessed lower limb power performance before and immediately after the match. Fluid loss was determined by body mass weighing before and after the end of the match. Te and wet-bulb globe temperature (WBGT) parameters were continuously recorded. The matches occurred across Te ranging from ~20.0 °C to 43.0 °C. Physical demands, CMJ height, peak heart rate (HRpeak), mean heart rate (HRmean), and RPE were not correlated with Te. However, a significant correlation was found between fluid loss and Te (r [95% CIs] = 0.67 [0.43–0.75]; p < 0.001). Beach soccer players maintained physical performance independent of Te. The specific characteristics of the sport may have promoted adequate thermoregulatory adaptations, helping maintain the players’ physical performance, particularly in matches played under high Te conditions. Elite beach soccer players maintained their physical performance independently of Te and despite experiencing dehydration (a body mass decrease of more than 2%) when the Te exceeded 35 °C.